2016
DOI: 10.1128/aem.03916-15
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Haloalkane Dehalogenase Inhibitors

Abstract: bHaloalkane dehalogenases (HLDs) have recently been discovered in a number of bacteria, including symbionts and pathogens of both plants and humans. However, the biological roles of HLDs in these organisms are unclear. The development of efficient HLD inhibitors serving as molecular probes to explore their function would represent an important step toward a better understanding of these interesting enzymes. Here we report the identification of inhibitors for this enzyme family using two different approaches. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Further assessment on the DUD dataset showed that NNScore 2.0 did not perform as well as NNScore 1.0 on average, but outperformed AutoDock, AutoDock Vina and Glide HTVS . In addition, NNScore was also involved in the discovery of inhibitors towards several important targets, which further testified its practicality …”
Section: Traditional Machine Learning Methods In Scoring Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further assessment on the DUD dataset showed that NNScore 2.0 did not perform as well as NNScore 1.0 on average, but outperformed AutoDock, AutoDock Vina and Glide HTVS . In addition, NNScore was also involved in the discovery of inhibitors towards several important targets, which further testified its practicality …”
Section: Traditional Machine Learning Methods In Scoring Functionsmentioning
confidence: 99%
“…132 In addition, NNScore was also involved in the discovery of inhibitors towards several important targets, which further testified its practicality. [133][134][135][136][137] Ouyang et al 115 developed a method named CScore that was trained by using a modified Cerebellar Model Articulation Controller learning architecture for binding affinity prediction. Similar with RF-Score, this method also relied on simple element-element atom pairs but used fuzzy membership functions rather than directly counting the occurrence to represent each feature.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Tools similar to the EcoliTox server could be integrated into a computational framework for improved design of native or heterologous biodegradation pathways and used to fine-tune their expression in selected microbial hosts. A powerful virtual screening approach, currently applied predominantly in drug design studies (Buryska et al, 2016), could be used similarly…”
Section: Figure 2 Herementioning
confidence: 99%
“…A major deviation in the catalytic groups of HLDs and other non-hydrolytic enzymes such as the 4-chlorobenzoyl-coenzyme A dehalogenase is seen with the essential tryptophan residues in which two Trp 175,125 residues form a binding pocket for the incipient halide ion [ 19 ]. Initially, carboxylate oxygen of the aspartate launches a nucleophilic attack on the carbon atom of the substrate that is bonded with halogen [ 14 , 18 , 19 , 20 , 21 , 61 , 69 , 70 ]. It can be clearly seen from that the aspartate acts as nucleophile and histidine as base for different type of haloalkane dehalogenases but the acid can be glutamate or aspartate and the two halide-stabilizing residues can be any combination formed by tryptophan and asparagine mostly.…”
Section: Introductionmentioning
confidence: 99%